Energy harvesting from human motion: exploiting swing and shock excitations. (14th January 2015) - Ylli, K; Hoffmann, D; Willmann, A; Becker, P; Folkmer, B; Manoli, Y
Abstract: Modern compact and low power sensors and systems are leading towards increasingly integrated wearable systems. One key bottleneck of this technology is the power supply. The use of energy harvesting techniques offers a way of supplying sensor systems without the need for batteries and maintenance. In this work we present the development and characterization of two inductive energy harvesters which exploit different characteristics of the human gait. A multi-coil topology harvester is presented which uses the swing motion of the foot. The second device is a shock-type harvester which is excited into resonance upon heel strike. Both devices were modeled and designed with the key constraint of device height in mind, in order to facilitate the integration into the shoe sole. The devices were characterized under different motion speeds and with two test subjects on a treadmill. An average power output of up to 0.84 mW is achieved with the swing harvester. With a total device volume including the housing of 21 cm 3 a power density of 40 μ W cm − 3 results. The shock harvester generates an average power output of up to 4.13 mW. The power density amounts to 86 μ W cm − 3 for the total device volume of 48 cm 3 . Difficulties and potential improvements are discussed briefly.